Buku Ajar berbasis Instructional Approach Learning pada Mata Kuliah Pendidikan Agama Hindu Berwawasan Multikultural - I Wayan Wira Darma; Ni Luh Purnamasuari Prapnuwanti; Komang Dewi Susanti (Journal for Lesson and Learning Studies, 2022)
Teaching materials are an essential component of the learning process. The existence of teaching materials that are by the characteristics and curriculum will foster good interaction in the learning process. This is the reason for the research, which aims to produce textbooks based on an instructional approach to learning in Hindu religious education courses with a multicultural perspective. Research and development methods (Research and Development). The sample is part or representative of the population that the researcher sampled. From the population determined above, the sample used in research is lecturers who teach Hindu religious education courses.Questionnaires are data collection techniques that are carried out by providing written questions to respondents to answer. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The study results showed that the developed Hindu religious education textbooks were suitable for learning. It can be seen from material experts, media experts, user responses, lecturers’ responses, and students’ responses. The textbooks that the researchers developed included very feasible criteria and good categories. It is recommended that the developed teaching materials be used as learning resources.